Analysis of Farmers' Response to The Rice Farm Insurance Program (AUTP) - Faqih, Achmad; Aisyah, Siti; Gunawan, Agun; Sutriyadi, Entris; Arifin, Jaenal; Supriatna, Supriatna (Eduvest - Journal of Universal Studies, 2023)
Rice farming experiences uncertainty and is a business that is very vulnerable to climate change such as natural disasters, floods and droughts, and is inseparable from attacks by plant-disturbing organisms (OPT), which result in decreased production and income of rice farmers. Agricultural Insurance is a transfer of risk that can provide compensation for losses due to farming so that the sustainability of farming can be guaranteed. This study aims to: 1) Know the response of farmers to the rice farming insurance program plan. 2) Knowing the response of farmers to the implementation of the rice farming insurance program and 3) Knowing the response of farmers to the impact of the farming insurance program. This study uses descriptive quantitative research methods with survey research techniques. Respondents consisted of the number of farmers who took part in the rice farming insurance program at least 2 times using the census technique with a total sample of 29 people. Data analysis technique using descriptive quantitative analysis. The results showed that: 1) The response of farmers to the planned rice farming insurance program in Gapoktan, Patalagan Village, Pancalang District, Kuningan Regency was very good. 2) The response of farmers to the implementation of the rice farming insurance program in Patalagan Village is good. 3) The response of farmers to the impact of the rice farming insurance program in Patalagan Village, Pancalang District, Kuningan Regency is Good.